PENERAPAN PEMBELAJARAN INVESTIGASI KELOMPOK UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS DITINJAU DARI INTELLIGENCE QUOTIENT SISWA - Raudatus Solihah; Agus Abhi Purwoko; Erin Ryantin Gunawan (Jurnal Penelitian Pendidikan IPA, 2016)
This research aims to know the effect of group investigation learning on student’s science process skill based on their IQ in SMAN 1 Mataram for eleventh grade students. This is a quasi experimental study using pretest postest control group design design. Pretest was taken to get data of student’s IQ. Posttest was also conducted to measure student’s science process skill. Sample was taken using nonprobability sampling from the population of eleventh grade student in SMAN 1 Mataram.The sample was two group of student each from two class, class XI sains 6 and as experimental group and class XI sains 5 as control group. The average os Student’s IQ on experimental group and control group were equal, both at 112. Learning processes were 12 x 45 minutes long in total. The experimental group showed better average score on posttest where they scored 82.40 on average, while control group only scored 74.83 on average. This value is statistically significant, at p = 0.007, less that 0.005. This result shows that implementation of group investigation can increase student’s science process skill.Keywords: Group investigation, science process skill, intelligence Quotient (IQ)ABSTRACT